Factors influencing mental health and oral health-related quality of life in population with recurrent aphthous stomatitis: a cross-sectional study - Weng, Siwei; Li, Shujia; Hou, Sicong (Frontiers in Oral Health, 2025)
BackgroundRecurrent episodes-induced oral functional limitations exacerbate anxiety, depression, and oral health-related quality of life (OHRQoL) impairments in Recurrent aphthous stomatitis (RAS) patients. However, the specific factors driving these psychological and OHRQoL deteriorations remain incompletely understood.ObjectivesWe aimed to quantify psychological distress and OHRQoL impairments in RAS patients and to identify modifiable risk factors underlying these deteriorations to inform targeted interventions.MethodsThis cross-sectional study surveyed RAS patients via an online/paper questionnaire. Demographic data, clinical information, the level of anxiety, depression and OHRQoL were collected and analyzed.ResultsProlonged ulcer duration and preference for Traditional Chinese Medicine (TCM) interventions are significant risk factors for the development of anxious and depressive symptoms in RAS patients. Frequent consumption of fried foods (OR: 3.88, p = 0.006) increases the risk of anxiety. Patients with high fruit intake frequency (B: 3.42, p < 0.001) exhibit more severe anxiety symptoms. Spicy food intake (B: −1.18, p < 0.001) has a mitigating effect on anxiety. Anxious RAS patients with frequent vegetable intake (B: −4.820, p < 0.001) experience reduced anxiety levels. Larger ulcer diameter (B = 2.09, p = 0.017), higher ulcer recurrence frequency (B = 4.74, p < 0.001), and frequent consumption of fried foods (B = 2.19, p = 0.002) exacerbate depressive symptoms in depressive RAS patients. Worsening of pain, frequent consumption of fried foods (B = 2.68, p = 0.004), moderate fruit intake (B = 1.39, p = 0.019), and preference for TCM interventions (B = 2.08, p = 0.022) demonstrate poorer OHRQoL.ConclusionsUlcer characteristics, dietary habits, and preference for TCM interventions were impairing risks for psychological distress and OHRQoL in RAS patients. Therefore, personalized psychological interventions should maintain control of mental health and OHRQoL, thereby reducing ulcer recurrence and improving outcomes.